Anti-angiogenesis and anti-metastasis effects of Polyphyllin VII on Hepatocellular carcinoma cells in vitro and in vivo - Chao Zhang; Qingrui Li; Guozheng Qin; Yi Zhang; Chaoying Li; Liwen Han; Rongchun Wang; Shudan Wang; Haixia Chen; Kechun Liu; Chengwei He (BMC, 2021)
Abstract Background Polyphyllin VII (PP7), a steroidal saponin from P. polyphylla has been found to exert strong anticancer activity. Little is known about the anti-angiogenesis and anti-metastasis properties of PP7. In this study, the anti-angiogenic and anti-metastatic effects of PP7 on HCC and the molecular mechanisms were evaluated. Methods Effect of PP7 on angiogenesis was assessed by tube formation assay and applied a transgenic Tg(fli1:EGFP) zebrafish model. Effects of PP7 on tumor metastasis and invasion were examined in cell migration and invasion assay, zebrafish tumor xenograft models and lung metastasis mouse models. The protein levels were examined by Western blotting. Results PP7 significantly decreased the tube formation of human umbilical vein endothelial cells, the number and length of ISVs and SIVs of transgenic zebrafish, and the metastasis and invasion of cancer cells in vitro and in vivo. The anti-angiogenic and anti-metastatic effects of PP7 in HepG2 cells were attributable, at least partially, to downregulated NF-κB/MMP-9/VEGF signaling pathway. Conclusion This study demonstrates that PP7 possesses strong anti-angiogenesis and anti-metastasis activities, suggesting that PP7 could be a potential candidate agent for HCC treatment.